Managingtomato bacterial wilt by suppressing Ralstonia solanacearum population in soil and enhancing host resistance through fungus-derived furoic acid compound - Ye, Meijin; Feng, Hong; Hu, Jianghong; Yu, Qing; Liu, Songqing (Frontiers in Plant Science, 2022)
Synthetic chemical pesticides are primarily used to manage plant pests and diseases, but their widespread and unregulated usage has resulted in major health and environmental hazards. Using biocontrol microbes and their bioactive compounds is a safe and sustainable approach in plant protection. In this study, a furoic acid (FA) compound having strong antibacterial activity against soil borne phytopathogenic bacterium Ralstonia solanacearum (causal agent of bacterial wilt; BW disease) was isolated from A. niger and identified as 5-(hydroxymethyl)-2-furoic acid compound through spectroscopic analyses (LC-MS, EI-MS, and NMR). SEM study of bacterial cells indicated the severe morphological destructions by FA compound. The FA was further evaluated to check its potential in enhancing host resistance and managing tomato BW disease in green house experiment and field tests. Results showed that FA significantly enhanced the expression of resistance related genes (PAL, LOX, PR1 and PR2) in tomato and caused significant reduction (11.2 log10 cfu/g) of R. solanacearum population in soil, resulting in the reduction of bacterial wilt disease severity on tomato plants and increase in plant length (58 ± 2.7 cm), plant biomass (28 ± 1.7 g) and root length (13 ± 1.2 cm). The findings of this study suggested that fungal derived FA compound can be a potential natural compound of biological source for the soil borne BW disease in tomato.